Coordination Motor Skills of Military Pilots Subjected to Survival Training. Issue 9 (September 2015) - Tomczak, Andrzej
Abstract : Abstract: Tomczak, A. Coordination motor skills of military pilots subjected to survival training. J Strength Cond Res 29(9): 2460–2464, 2015—Survival training of military pilots in the Polish Army gains significance because polish pilots have taken part in more and more military missions. Prolonged exercise of moderate intensity with restricted sleep or sleep deprivation is known to deteriorate performance. The aim of the study was thus to determine the effects of a strenuous 36-hour exercise with restricted sleep on selected motor coordination and psychomotor indices. Thirteen military pilots aged 30–56 years were examined twice: pretraining and posttraining. The following tests were applied: running motor adjustment (15-m sprint, 3 × 5-m shuttle run, 15-m slalom, and 15-m squat), divided attention, dynamic body balance, handgrip strength differentiation. Survival training resulted in significant decreases in maximum handgrip strength (from 672 to 630 N), corrected 50% max handgrip (from 427 to 367 N), error 50% max (from 26 to 17%), 15-m sprint (from 5.01 to 4.64 m·s −1 ), and 15-m squat (2.20 to 1.98 m·s −1 ). The training improvements took place in divided attention test (from 48.2 to 57.2%). The survival training applied to pilots only moderately affected some of their motor adjustment skills, the divided attention, and dynamic body balance remaining unaffected or even improved. Further studies aimed at designing a set of tests for coordination motor skills and of soldiers' capacity to fight for survival under conditions of isolation are needed.